(untitled) (Annals of Medical Research, 2023)
Aim: This study examined inflammation markers and electrocardiogram data in patients with first-episode mania (FEM). It aimed to examine the inflammation processes in the early stages of the disease and the frontal QRS-T (fQRS-T) angle in bipolar disorder (BD). Materials and Methods: After exclusion criteria, 53 FEM patients and 59 healthy controls (HC) were included in the study. Sociodemographic, electrocardiogram (ECG) and lab data of the participants were evaluated. Results: Mean of age and gender distribution did not differ between the groups (p=.743, p=.294, respectively). The heart rate of the FEM group was significantly higher than the HC group (p<.001). fQRS-T was significantly wider in the FEM group than in healthy controls (p=.20). Albumin was significantly lower in the FEM group than in the HC group (p<.001). CRP and CAR values ​​were significantly higher in the FEM group than in HC (p=.009 and p=.011, respectively). In the FEM group, HDL value was significantly lower than HC, while LDL value was significantly higher than HC (p=<.001 and p=.001, accordingly). MHR and AIP values ​​were significantly greater in the FEM group than in HC (p=<.001 and p=.006, respectively). The fQRS-T angle in FEM patients was associated with MHR (r=.37). Conclusion: This study is unique in evaluating inflammatory markers, fQRS-T angle, and heart rate in FEM patients. In this study, we found significantly higher inflammatory markers of MHR, CRP, and CAR in FEM patients in the control group. We found that these findings were consistent with the literature. Since the fQRS-T angle was wider in the FEM group, the cardiovascular risk may be increased in the early stages of BD disease.